Analysis of the Role of Work Environment and Leadership Style in Improving Service Performance at Automotive Industry - Deti Mulyo Harsono; Mulyawan Hardi; Astri Amanda (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The automotive industry in Indonesia contributes 2.1% to the national GDP but was heavily affected by the Covid-19 pandemic, causing declines in demand and service revenue. To recover, companies must improve service quality through better work environments and leadership practices. Objective: This study analyzes the role of the work environment and leadership style in improving service performance at Automotive Industry. Method: Using a quantitative approach, data were collected from 138 service advisors and analyzed with PLS-SEM to examine validity, reliability, and relationships among variables. Result: The work environment significantly affects leadership style (β = 0.770, p = 0.000), which positively influences service performance (β = 0.497, p = 0.000). Although the direct effect of the work environment on service performance is smaller (β = 0.289, p = 0.010), the total impact is stronger due to leadership’s mediating role (indirect effect = 0.382). Conclusion: Asupportive workenvironment enhances leadership effectiveness, which leads to better service performance. Originality/Value (State of the Art): This study is among the first to empirically examine leadership style as a mediating variable linking work environment to service performance, specifically among service advisors in automotive industry. By situating the analysis within Indonesia’s automotive service sector during the post-pandemic recovery period, this research extends the DeLone and McLean organizational performance framework to the dealer-level service context, addressing a gap in the literature on human-centered performance drivers in competitive automotive retail settings.